THE EFFECT OF USING HERO QUEST STRATEGY TOWARD THE STUDENTS WRITING SKILL OF RECOUNT TEXT AT TENTH GRADE STUDENTS OF STATE SENIOR HIGH SCHOOL 2 KUOK KAMPAR REGENCY - Oding Fahma Imani; Lusi Marleni (Journal of English Language and Education, 2019)
This research was carried out based on researcher’s preliminary study at State Senior High School 2 Kuok at tenth grade in academic year 2016/2017. In this researcher use quasi experimental research with pottest only. The aim of this research is to find out the effectiveness of the use Hero Quest Strategy in teaching writing skills on recount text. The researcher took two classes as the samples were class X1 as the control group and class X2 as the experimental class. Total sampling technique we used by the researcher to take the sample. The technique of data collection was test. Meanwhile, to analyze the data, the researcher used Independent Samples T-test formula by using SPSS 20.0 Version. Based on the analysis data the result showed that the average student posttest in experimental class were 72.47, and in control class has average students posttest were 54.31. The researcher used T-test, the result of the average test calculating (T-test) 0.000. It was proved that this research was 0.000